Response of Rice Plant to Application of Nanoparticles of Fe and Zn at Elevated CO2: A Hydroponic Experiment under Phytotron - Yadav, Ramesh Chandra; Patra, A. K.; Purakayastha, T. J.; Bhattacharyya, R.; Singh, R. (International Journal of Bio-resource and Stress Management, 2023)
Hydroponic experiments were conducted inside the phytotron growth chambers for investigating the response of rice plant to nanoparticles of Fe and Zn under ambient (390±10 ppm) and elevated (610±10 ppm) atmospheric CO2 concentration. The 100, 500, 1000 ppm n-Fe2O3 or n-ZnO and FeSO4 or ZnSO4 were supplied. At 500 ppm concentration of both n-Fe2O3 and n-ZnO particles, highest accumulation of Fe and Zn to the extent of 1471 mg kg−1 and 1158 mg kg−1 respectively, was recorded. The trend in accumulating Fe or Zn among the treatment was 500 ppm>1000, ppm>100, ppm>FeSO4 or ZnSO4>control. Irrespective of treatments concentration of Fe and Zn was highest in root followed by stem and leaf. At elevated CO2 concentration the accumulation of Fe or Zn was increased in all the plant parts.